Numerical and experimental investigations of the electrodeposition process on open porous foams, determination of the parameter influence on the coating homogeneity. (December 2021) - Grill, C.; Fries, M.; Jung, A.; Diebels, S.
Highlights: Improved and prediction of mass transport limitation during electrodeposition. Comparison of numerical simulations and experimental results. Increase of velocity and diffusivity increases coating thickness homogeneity. Decrease of deposition parameters increases coating thickness homogeneity. Migration has only a negligible influence on the coating thickness homogeneity. Abstract: The limited quantity of raw materials leads to application-optimised materials, such as open-cell hybrid foams. A nanocrystalline nickel coating significantly enhances the crash absorber properties of aluminum and PU foams with only a small increase in weight. The coating is applied by an electrodeposition process. Due to mass transport limitations during the process, an inhomogeneous coating thickness is created resulting in inhomogeneous material properties. To avoid different coating thicknesses at different points of the foam, the electrodeposition process in the foam is modelled and simulated. The results of the simulation are compared with experimental data and the influence of different parameters on the coating homogeneity is investigated by means of simulation.